Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone via Rh-catalyzed diastereoselective oxidative C-H aminations - Narina, Srinivasarao V.; Kumar, Talluri Siva; George, Shyla; Sudalai, Arumugam (Tetrahedron Letter, 2007)
An efficient enantioselective synthesis of (-)-cytoxazone (1) and (+)-epi-eytoxazone (2) using proline-catalyzed asymmetric alpha-amino-oxylation of aldehydes followed by Rh-catalyzed diastereoselective oxidative C-H amination as the key steps is described. syn or anti 1,2-aminoalcohols were obtained by Rh-catalyzed intramolecular amidation of the C-H bonds of carbamates or sulfamate esters with good to excellent diastereoselectivity. (c) 2006 Elsevier Ltd. All rights reserved.